Early experiences with edoxaban for stroke prevention in atrial fibrillation in the Southeast Asia region - Bimbo Diaz, Alejandro; Chow, Jeremy; Fan, Kee Hoo; Kok, Wei Koh; Chin, Gary Keong Lee; Wee, Siong Teo; Venketasubramanian, Narayanaswamy; Chun, Chieh Wang; Mehta, Radhika (Bioexcel Publishing, 2023)
Edoxaban, a once-daily, direct-acting oral anticoagulant, is approved to prevent stroke or systemic embolism in non-valvular atrial fibrillation (NVAF) and treat venous thromboembolism. The clinical benefit of edoxaban for stroke prevention in Asian patients with NVAF has been demonstrated in clinical and real-world studies. We share early clinical experiences with once-daily edoxaban and discuss its evidence-based use in patients with NVAF in Southeast Asia through several cases of patients at high risk, including frail patients, elderly patients with multiple comorbidities and patients with increased bleeding risk. These cases demonstrate the effectiveness and safety of once-daily edoxaban in patients with NVAF in Southeast Asia.